(untitled) (Journal of Business Management and Accounting, 2019)
This study attempts to identify hotels service attributes that influence tourists’ satisfaction in the context of Cox’s Bazar, Bangladesh. Descriptive research was conducted to gain an insight into the topic and to investigate the factors. This paper reports findings based on a descriptive study. To conduct this study, a survey was administered to 300 respondents using a non-probability sampling which is a convenience sampling technique. To analyze the data, factor analysis, correlation, regression analysis and frequency distribution table was used. A conceptual model of tourist’s satisfaction based on service attributes of hotels in Cox’s Bazar was proposed based on factor and regression analysis. Seven factors emerged and were used as independent variables in the regression analysis. Findings indicate that some hotel service attributes have a direct influence on tourists’ satisfaction which make them loyal in the context of Cox’s Bazar.